The Influence of Work Discipline on Employee Performance at the Rengas Ciputat Timur Village Office, South Tangerang City - Rio Pratama; Anshori Anshori (Universitas Persada Indonesia YAI, 2025)
This study, conducted by Rio Pratama, This study aims to examine the effect of work discipline on employee performance at the Rengas Village Office, Ciputat Timur Subdistrict, South Tangerang City. Employing a quantitative approach with simple linear regression analysis, the study involved the total population of 27 employees using a total sampling technique. Data were collected via questionnaires and analyzed using t-tests, F-tests, and the coefficient of determination (R²). The regression equation derived is: Y = 17.569 + 0.615X, which indicates that every one-unit increase in work discipline leads to a 0.615-unit increase in employee performance. The t-test results showed a t-value of 5.885, exceeding the critical value of 1.706, with p = 0.000 (< 0.05), signifying that work discipline has a significant partial effect. The F-test yielded an F-value of 34.635, which is greater than the critical value of 3.37, with p = 0.000 (< 0.05), confirming that work discipline has a significant simultaneous effect on performance. The coefficient of determination (R² = 0.581) indicates that work discipline accounts for 58.1% of the variance in employee performance, while the remaining 41.9% is explained by other variables outside this study. In conclusion, the findings suggest that improving work discipline is an effective strategy for enhancing employee performance